Pollinators adjust their behavior to presence of pollinator-transmitted pathogen in plant population. (24th January 2022) - Koupilová, Klára; Štenc, Jakub; Janovský, Zdeněk
Abstract: Interactions between pollinators and plants can be affected by presence of plant pathogens that substitute their infectious propagules for pollen in flowers and rely on pollinators for transmission to new hosts. However, it is largely unknown how pollinators integrate cues from diseased plants such as altered floral rewards and floral traits, and how their behavior changes afterwards. Understanding pollinator responses to diseased plants is crucial for predicting both pathogen transmission and pollen dispersal in diseased plant populations. In this study, we investigated pollinator responses to contact with plants of Dianthus carthusianorum diseased with anther smut ( Microbotryum carthusianorum ). We combined three approaches: 1) observation of individual pollinators foraging in experimental arrays of pre-grown potted plants; 2) measurements of floral rewards and floral traits of healthy and diseased plants; and 3) quantification of pollen/spore loads of pollinator functional groups. We found that pollinators showed only weak preferences for visiting healthy over diseased plants, but after landing on plants, they probed fewer flowers on the diseased ones. Since diseased flowers offered lower nectar and no pollen rewards, this behavior is consistent with the prediction of optimal foraging models that pollinators should spend less time exploring less rewarding patches or plants. Furthermore, pollen-foraging solitary bees and hoverflies responded to diseased plants more negatively than nectar-feeding butterflies did. Lastly, based on group-specific behavior and typical pollen/spore loads, we suggest that solitary bees and hoverflies contribute to both pollen and pathogen spore dispersal mainly over short distances, while butterfly visits are most important for long-distance dispersal. Abstract : Pollinators try to avoid visiting flowers infected with pathogens because these flowers offer them lower rewards. Using a grassland perennial and its anther smut pathogen, we show that pollinators are not highly successful in recognizing infected plants from a distance and subsequently avoiding them. However, after landing on plants, pollinators adjust their behavior and leave poorly rewarding infected plants sooner. Pollinators therefore move more among plants and this behavior could enhance pathogen spread.